Effect of Application of Botanical Pesticida xtracts of Citrus (Citrus aurantifolia) and Betel (Piper betle) Leaves on the Mortality of the Pest (Plutella xylostella) on Jengkol (Phitecellobium jiringa) plants - Muhammad Mardhiansyah; Putri Cahyani; Pebriandi; Ewi Irfani; Ika Lestari; Niskan Walid Masruri (Jurnal Ilmu Ilmu Kehutanan, 2024)
Plutella xylostella are one of the pests that attack BPDASHL (Watershed against hanging Plutella xylostella pests on Phitecellobium jiringa plants. This study botanical pesticide, used a completely randomized design (CRD), with the treatments namely: P1 = a pest control, Citrus mixture of C. aurantifolia leaf extract and P. betle leaf 50 g/L, P2 = a mixture of C. aurantifolia, Piper aurantifolia leaf extract and P. betle leaf 100 g/L, P3 = a mixture of C. aurantifolia betle, nursey leaf extract and P. betle leaf 150 g/L, and P4 = a mixture of C. aurantifolia leaf extract and P. betle leaf 200 g/L. The observation variables in this study were temperature and humidity, the initial time of death, lethal time50 (LT50), daily mortality, and total mortality. The results showed that the application of botanical pesticide extract of C. aurantifolia leaf and P. betle leaf was efficient on the mortality of hanging P. xylostella pests with a total mortality result of 100%. The best the best concentration is a mixture of C. aurantifolia leaf extract and P. betle leaf 200 g/L (P4).